Global minimum tax and profit shifting - Tomáš Boukal; Petr Janský; Miroslav Palanský (Charles University in Prague, Institute of Economic Studies (IES), 2024)
We develop a methodology to decompose the tax revenue impact of the global minimum tax introduced in 2024 into several components and quantify its potential impact on profit shifting. We apply it to 34 thousand multinational-country observations from tax returns, financial statements and country-by-country reports of all multinationals active in Slovakia. We find that the global minimum tax has the potential to decrease profit shifting by most multinationals, which are on average likely to pay higher effective tax rates in most countries worldwide post-reform. We find that Slovak corporate tax revenues will increase by 4%, with half of the increase due to its minimum top-up taxes. The other half of the increase is corporate income tax on profits that will no longer be shifted out of the country. We expect the global minimum tax to target 49% of previously shifted profits.
Keywords: H25; H26; 330; global minimum tax; profit shifting; multinationals; tax avoidance